Implementasi Sistem First to File Terhadap Pembatalan Merek Karena Itikad Tidak Baik (Studi Terhadap Putusan Mahkamah Agung Nomor 640 K/Pdt.Sus-HKI/2020) - Vitadiani, Asri (MIH FH UNSOED, 2023)
Trademarks as a form of protection for Intellectual Property Rights (IPR) have been used for a long time and have an important role, because the brand is one of the strategic efforts to promote business to the wider community. The number of creations causes the need to protect goods or services which in the production process use Intellectual Property Rights, to avoid the possibility of counterfeiting or unfair competition. Mark ownership rights based on laws and regulations are obtained through a constitutive registration system with the First to File principle, which means that trademark rights are acquired only for those who register for the first time. The reality is that there are still many cases of brand abuse committed by parties with bad intentions. The main issues discussed in this paper are the application of the First to File system in terms of ownership rights to the Samgong brand and the judge's considerations in deciding cases on the Supreme Court's decision Number 640 K/Pdt.Sus-HKI/2020. The type of research method used in this paper is a type of juridical-normative legal research method consisting of a statutory approach, a case approach and a conceptual approach. The results of the study on the decision of the Supreme Court Number 640 K/Pdt.Sus-HKI/2020 on the dispute over the Samgong brand, it can be said that the first to file system in the dispute has not been implemented. The judge also did not include international provisions as a consideration in deciding the dispute over the Samgong trademark. Keywords: Brand, First to File System, Bad Faith